Glycolytic and chitinolytic activities of Phlebotomus papatasi (Diptera: Psychodidae) from diverse ecological habitats - Jacobson, Raymond L; Studentsky, Liora; Schlein, Yosef (Folia parasitologica, 2007)
The sand fly Phlebotomus papatasi Scopoli, 1786, the vector of Leishmania major Yakimoff et Schokhor, 1914, is found in desert areas where sugars are scarce but also in habitats that abound in sugar sources. The sand flies require sugar meals from plant sources for their energy requirements and to hydrolyze these complex sugars, they need a repertoire of glycosidases. We presumed that there are differences in the levels of glycosidase activities in flies from such habitats and also assumed that they may be instrumental in modulating the flies' susceptibility to L. major infections. Phlebotomus papatasi originating from diverse ecological habitats ranging from an oasis to desert sites were colonized. They were analyzed for weight changes and glycosidase activities before and after feeding on 1M sucrose solution. Oasis flies were smaller than desert flies but took larger sugar meals. Homogenates of these flies hydrolyzed 16 synthetic and 2 natural glycoside substrates to varying degrees. The arid-region flies tended to produce more glycosidase activity than those originating in sugar-rich environments, especially sucrase, alpha- and beta-glucosidase, aalpha-fucosidase, alpha-mannosidase, and alpha- and beta-N-acetylgalactosaminidase. However, chitinolytic enzyme activities and particularly the beta-N-acetylhexosaminidase activity of oasis flies were higher than other flies tested. In comparing the desert flies, there were also significant differences in glycolytic enzyme activities between the spring-line (flowering season) of flies and the autumn-line (end of dry season) flies. A range of saccharide inhibitors was tested to demonstrate the specificity of the enzymes.
Keywords: Leishmania major; Analysis of Variance; Animals; Chitin; Enzymes; Female; Insect Vectors; ženské pohlaví; Sucrose; chitin; Phlebotomus; Sex Factors; tělesná hmotnost; hmyz - vektory; analýza rozptylu; Male; sexuální faktory; Body Weight; ekosystém; Ecosystem; zvířata; mužské pohlaví; sacharosa; enzymy